Use of a self-cemienting fly ash as a soil stabilization agent - Nalbantoglu, Z (Shiraz Univ, 2001)
The increasing trend towards electrical power generation through coal combustion has aggravated the problems associated with disposal of the fly ash produced as a by-product. Due to the pozzolanic properties of fly ash, it can be utilized as a soil stabilizer. In this study, the calcareous expansive soil in Cyprus has been stabilized with different percentages of fly ash and the results are discussed. Scanning electron micrographs (SEM) show that the new tobermorite minerals formed from the gelatinous reaction products are responsible for the long-term strength development of soils. Due to its mineralogical composition, unlike to the expected soil behavior, the long-term strength development of this soil is obtained below lime modification optimum (LMO). Increasingly, granular nature of the stabilized soils with time, results in a reduced water sorption potential. The use of fly ash with a small percentage of lime produces even more dramatic results. The risk of lime and fly ash treatment of sulfate-bearing clay soils is discussed. The findings encourage the consideration of fly,ash as a possible alternative for the stabilization of calcareous expansive soils.
Keywords: calcareous; cementation; fly ash; lime; semi-arid; stabilization; strength; swell